The ambiguity of technology in ASMR experiences: Four types of intimacies and struggles in the user comments on YouTube - Klausen Helle Breth (Nordicom Review)
Autonomous sensory meridian response (ASMR) is a tingling, static-like sensation in response to specific triggering audio and visual stimuli. Within recent years, ASMR has mostly been associated with videos on YouTube (technologically mediated ASMR) dedicated to make the users “tingle”, relax, and feel at ease. In this article, I explore the ambiguity of technology in relation to the ASMR experience and theoretically investigate how viewer-listeners might struggle to obtain an intimate and parasocial interaction in a technologically mediated ASMR context. The article introduces four types of intimacies as well as theoretical concepts of mediated intimacy, immediacy, and parasocial interaction, and I discuss these intimacies and concepts in relation to illustrative comments by some of the pacesetting power users of ASMR.